(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2012)
A new genus of bryophytes Lazarenkia Boiko (Pottiaceae, Bryopsida) is described with giving the name in honour of famous Ukrainian bryologist A.S.Lazarenko. The genus Lazarenkia includes one species – Lazarenkia kozlovii.